The Impact of Liberalizing Barriers to Foreign Direct Investment in Services: The Case of Russian Accession to the World Trade Organization - Jensen, Jesper; Rutherford, Thomas; Tarr, David (World Bank, Washington, D.C., 2013)
The authors use a computable general equilibrium model of the Russian economy to assess the impact of accession to the World Trade Organization (WTO), which encompasses improved market access, tariff reduction, and reduction of barriers against multinational service providers. They assume that foreign direct investment in business services is necessary for multinationals to compete well with Russian business service providers, but cross-border service provision is also present. The model incorporates productivity effects in both goods and services markets endogenously through a Dixit-Stiglitz framework. As a result, the estimated gains from WTO accession are much larger than would be obtained from a typical model with perfect competition. The ad valorem equivalent of barriers to foreign direct investment have been estimated based on detailed questionnaires completed by specialized research institutes in Russia. The authors estimate that Russia will gain about 7.2 percent of the value of Russian consumption in the medium run from WTO accession and up to 24 percent in the long run. They estimate that the largest gains to Russia will derive from liberalization of barriers against multinational service providers. Piecemeal and systematic sensitivity analysis shows that their results are robust.